The genus Sakencyrtus Hayat (Hymenoptera: Chalcidoidea: Encyrtidae) from India with description of a new species - Usman, Syeda Uzma; Zeya, Shahid Bin (Zootaxa, 2018)
Indian species of the genus Sakencyrtus Hayat are reviewed and illustrated. A new species, Sakencyrtus bialbifuniculus sp. nov., is described. The two species known from India, S. mirus Hayat and S. albiclavus Hayat, are redescribed. The macropterous forms and males of S. mirus are described for the first time. An identification key to species is provided.